The impact of unions on wages in the public sector: Evidence from higher education - Michael Baker; Yosh Halberstam; Kory Kroft; Alexandre Mas; Derek Messacar (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
We study the effects of the unionization of faculty at Canadian universities from 1970-2022 using an event-study design. Using administrative data which covers the full universe of faculty salaries, we find strong evidence that unionization leads to both average salary gains and compression of the distribution of salaries. Our estimates indicate that salaries increase on average by 2 to over 5 percent over the first 6 years post unionization. These effects are driven largely by gains in the bottom half of the wage distribution with little evidence of any impact at the top end. Our evidence indicates that the wage effects are primarily concentrated in the first half of our sample period. We do not find any evidence of an impact on employment.
Keywords: 330